2017
DOI: 10.1038/s41593-017-0004-1
|View full text |Cite|
|
Sign up to set email alerts
|

Altered cerebellar connectivity in autism and cerebellar-mediated rescue of autism-related behaviors in mice

Abstract: Cerebellar abnormalities, particularly in Right Crus I (RCrusI), are consistently reported in autism spectrum disorders (ASD). Although RCrusI is functionally connected with ASD-implicated circuits, the contribution of RCrusI dysfunction to ASD remains unclear. Here, neuromodulation of RCrusI in neurotypical humans resulted in altered functional connectivity with the inferior parietal lobule, and children with ASD showed atypical functional connectivity in this circuit. Atypical RCrusI–inferior parietal lobule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
274
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(319 citation statements)
references
References 88 publications
(112 reference statements)
17
274
4
1
Order By: Relevance
“…Additionally, we observed that DAN connectivity with subcortical regions, primarily the putamen/lentiform nucleus and cerebellum, was uniquely associated with stereotyped behavior. These findings provide further empirical support for significant involvement of cortico-striatal-thalamo-cortical circuitry in stereotypies (7072). Further, atypical recruitment and regulation of visual cortical regions and atypical visual attention have been linked with RRB symptomology (7375) and abnormalities in the control of visual attention have been shown to persist throughout infancy in children who are later diagnosed with ASD (23, 7678).…”
Section: Discussionsupporting
confidence: 63%
“…Additionally, we observed that DAN connectivity with subcortical regions, primarily the putamen/lentiform nucleus and cerebellum, was uniquely associated with stereotyped behavior. These findings provide further empirical support for significant involvement of cortico-striatal-thalamo-cortical circuitry in stereotypies (7072). Further, atypical recruitment and regulation of visual cortical regions and atypical visual attention have been linked with RRB symptomology (7375) and abnormalities in the control of visual attention have been shown to persist throughout infancy in children who are later diagnosed with ASD (23, 7678).…”
Section: Discussionsupporting
confidence: 63%
“…In normal mice, chemogenetic inhibition of right Crus I Purkinje cells resulted in both increased parietal single cell firing rates (potentially through disinhibition of excitatory deep cerebellar nuclei efference) as a measure of cerebello-parietal connectivity and reduced preference for social novelty as a marker of social behavior, not explained by sensorimotor or visual deficits. Furthermore, chemogenetic activation of right Crus I Purkinje cells in the mutant mice reduced left parietal firing rates and specifically improved social interaction (Stoodley et al, 2017). These data suggest cerebrocerebellar connectivity and resulting pro-social behavior may be restored through stimulation of Crus I.…”
Section: Promising Translational Approachesmentioning
confidence: 63%
“…For us, an important motivation for building a lighter and smaller miniscope was the ability to record from two regions concurrently in unrestrained mice and in particular to obtain cellular resolution recordings of cerebellum and cerebral cortex. There is ample anatomical evidence for cerebello-thalamo-cerebral loops (Hoover and Strick 1999;Akkal, Dum, and Strick 2007;Bostan, Dum, and Strick 2013) and an increasing number of studies suggest that functional interactions within such loops are important for the proper expression of social, cognitive and motor (planning) behaviors (Badura et al 2018;Stoodley et al 2017;Gao et al 2018) . The ability to record from both cerebellum and cortex simultaneously in unrestrained mice opens up the possibility to study how these interactions play out during natural spontaneous behaviors.…”
Section: Cellular Resolution Imaging Of Cerebello-cerebral Interactiomentioning
confidence: 99%